Evolution of Th1 and Th2 biased cytokines in divergent species of animals - KAUR, MANMEET; MUKHOPADHYAY, CHANDRA SEKHAR; ARORA, JASPREET SINGH; DHANOA, JASDEEP KAUR (The Indian Journal of Animal Sciences, 2019)
Proteins or peptides that play a major role in immune as well as inflammatory responses via activation and regulation of other cells and tissues are known as cytokines. Their role in mammals is well defined, with a vast number of publications describing the structure of cytokines and their role in health and disease. Total 22 full-length CDS (and corresponding peptide) of the domains were selected as representatives of each type of cytokine, belonging to divergent animal species, for the biocomputational analysis. The secondary and tertiary structure of the different cytokine (peptide sequence) domains was predicted to compare the relatedness among the domains under study. Multiple sequence alignment and phylogenetic tree results indicated that IFN-gamma formed separate clusters for mammals, avian, and fish. In IL12, all were dispersed except Canis lupus and Sus scrofa. In IL13, chicken was completely dispersed from mammals and closely related to IL8 and TNF. These interleukins could have evolved independently from the respective ancestral sequences.